Dropping Shock Characteristics of the Suspension Cushioning System with Critical Components. (13th November 2017) - Li, Hui; Chen, Anjun; Duan, Ningning
Abstract : Dimensionless dropping shock dynamic equations of suspension nonlinear packaging system with critical components were obtained. The numerical results of shock response were gained using Runge-Kutta method. To evaluate the dropping shock characteristics of critical components, the dropping damage boundary curve was established, where the system parameter and the dimensionless shock velocity were selected as two coordinate parameters. Then, the frequency ratio and the system damping ratio were taken as third basic parameters of the dropping damage boundary surface, respectively. To study dynamic properties of the suspension system with critical components, the shock response acceleration, shock response displacements, and dropping damage boundary were analyzed. Based on the numerical results, the effects of the relevant parameters on dropping shock response and damage boundary of critical component were investigated. It is demonstrated that both a higher frequency ratio and a system damping ratio in the specific range can exert a positive effect on the product protection and should be selected in design process of the suspension system. Furthermore, with the decrease of suspension angle, the acceleration response peak decreases, the displacement response peak increases, and the safety zone enlarges.